Factors influencing happiness among employees of public sector companies in Johor Bahru / Muhammad Ghazali Hamzah - Hamzah, Muhammad Ghazali (Faculty of Business and Management, 2018)
This study is conducted to determine the factor that influence the happiness among employees of public sector companies in Johor Bahru. In this study, samples are taken from two sub sectors which are corporate and education sub sectors that are represented by Johor Petroleum Development Corporation Berhad, JPDC and Faculty of Build Environment, Universiti Teknologi Malaysia, UTM respectively. The sample of the whole population from both of the companies are taken by using simple random sampling based on the sample frame provided by the Human Resource Department of the companies. Primary data was then collected using questionnaires method after one week of distribution. There are a few data analysis used in this study which are Pearson Correlation analysis, Multiple Regression analysis and ANOVA Test. Based on the result of Pearson Correlation analysis, all independent variables job position (IV1), income (IV2), relationship (IV3) and work engagement (IV4) are significantly correlated with the happiness among employees at workplace (DV). In addition, job position variable shows the highest correlation towards the happiness among employees at workplace. In addition, from the multiple regression model, only job position and relationship at workplace variables are significant with the happiness at workplace, while income and work engagement variables are not significant with happiness at workplace. Moreover, job position has the highest significant relationship with happiness at workplace as it has the highest Beta value of 0.552. Last but not least, the ANOVA test shows the significant difference between corporate and educational sub sector to determine the level of happiness between these sub sectors. The mean or education sub sector is slightly higher than corporate sub sector. Thus, assumption can be made that employees of education sub sector is happier than corporate sub sector.